Condições de trabalho e de vida domiciliar dos assalariados da agropecuária da Região Sul - Nascimento, Carlos Alves do; Staduto, Jefferson Andronio Ramundo; Mantovani, Gabriela Gomes (2024)
The article aims to measure the contingents of families of salaried workers in agriculture in the South region, and to analyze the working conditions and material home life of these workers. A typology of families and indices of work quality and living conditions were constructed based on microdata from the PNADs/IBGE from 2002 to 2014. The reference value for classifying the types of families was the minimum wage calculated by DIEESE. The period analyzed was one of considerable economic expansion and social development, in which the contingent of wage earners families who were in the worst social conditions was significantly reduced, but there was still a high participation of this number of wage earners in the sample analyzed in 2014.
O artigo tem como objetivo mensurar os contingentes de famílias de assalariados na agropecuária da região Sul, e analisar as condições de trabalho e de vida material domiciliar desses trabalhadores. Foi construído uma tipologia de famílias e índices de qualidade dos empregos e das condições de vida a partir dos microdados das PNADs/IBGE de 2002 a 2014. O valor de referência para a classificação dos tipos de famílias foi o salário mínimo necessário calculado pelo DIEESE. O período analisado foi de grande expansão econômica e desenvolvimento social, no qual se reduziu expressivamente o contingente de famílias de assalariados que se encontrava nas piores condições sociais, porém ainda se registrava elevada participação desse número de assalariados na amostra analisada em 2014.
Keywords: Working condition; Material life condition; Job quality; Minimum wage required; Condição de trabalho^lpt; Condição de vida material; Qualidade do emprego; Salário mínimo necessário